2000
DOI: 10.1080/095831500750016361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus thuringiensis var. israelensis on Target and Nontarget Organisms: A Review of Laboratory and Field Experiments

Abstract: Since the discovery of Bacillus thuringiensi s var. israelensis (Bti) in 1976, extensive literature has proved its eYcacy to control mosquitoes and black Xies, of which many species are known as important vectors of diseases or simply as pests of humans and animals. Since 1978, Bti has been used in many countries on all continents and numerous studies have been made on target mosquitoes and black Xies, as well as nontarget organisms (NTO). This review analyses the results of 75 studies on these organism s cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
145
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(161 citation statements)
references
References 59 publications
9
145
0
5
Order By: Relevance
“…Of particular relevance, no study has so far reported any direct significant effect of Bti and Bs to the organisms monitored in the current study. Significant adverse effects have been observed in certain dipterans when exposed to Bti, as summarized in a review by Boisvert (Boisvert & Boisvert, 2000). However, in most of these cases, treatments were either overdosed or the adverse effects were linked to other factors such as formulation additives, turbidity or methodological errors (Boisvert & Boisvert, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular relevance, no study has so far reported any direct significant effect of Bti and Bs to the organisms monitored in the current study. Significant adverse effects have been observed in certain dipterans when exposed to Bti, as summarized in a review by Boisvert (Boisvert & Boisvert, 2000). However, in most of these cases, treatments were either overdosed or the adverse effects were linked to other factors such as formulation additives, turbidity or methodological errors (Boisvert & Boisvert, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that lentic organisms are particularly more exposed to Bti and Bs than lotic organisms due to heavier accumulation of toxin in the former than the later ecosystem (Boisvert & Boisvert, 2000). With mosquito larval habitats being of the lentic ecosystem, there may be a possibility of accumulation of Bti and Bs toxins to levels that can impact non‐target organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Living near wetlands often entails serious health hazards for humans and animals due to increased risk of mosquito-borne diseases (Russell, 1999;Walton, 2002;Kirkman et al, 2011;Lagadic et al, 2014). To date, Bti represents the best alternative to chemical insecticides for mosquito control (Despre´s et al, 2011) and is described as non-toxic to humans, mammals, birds, fish, plants and most aquatic organisms (Boisvert and Boisvert, 2000;Lacey and Merritt, 2004). Bti is the only larvicide used in Europe following implementation of the EU Biocidal Products Directive 98/8/EC (Lagadic et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Les molécules à large spectre d'action ont ainsi progressivement cédé la place aux insecticides dits biologiques, comme le Bti (Bacillus thuringiensis var. israëlensis), plus sélectifs avec peu ou pas d'effets néfastes démontrés sur l'environnement (Becker et Margalit, 1993 ;Boisvert et Boisvert, 2000 ;Franquet et al, 2002). Ce bacille agit après ingestion, par des larves de Diptères, en libérant des toxines protéiques qui perforent l'épithélium intestinal et conduisent à leur mort.…”
Section: « Acrobaties Taxinomiques » Pour Un Enchevêtrement Entre Socunclassified